Electricity Supply and Economic Growth in Nigeria: A Bounds Testing Co-integrative Approach (Lapai Journal of Economics, 2019)
The paper examines empirically, whether or not electricity supply and investment in electricity impact significantly and positively on economic growth in Nigeria over the sample period of thirty-six year from 1980-2017. The newly developed bounds testing approach to co-integration was adopted in the study. The results obtained reveal that both the short-run and long-run growth effects of electricity supply in Nigeria are significant and positive. Having ascertained the significance of electricity supply positively influencing economic growth in Nigeria, the study thus recommends a set of policies to the Nigerian government with a view to enhancing electricity distribution and fostering economic growth in Nigeria.